Opinion of the B.Ed. Students about Teacher Eligibility Test (TET) - Raghuvansh, Sujata; Tiwari, Ajay Prakash (JOURNAL OF INDIAN EDUCATION, 2012)
The implementation of the Right of Children to Free and Compulsory Education (RTE) Act, 2009 requires the recruitment of a large number of teachers across the country in a time-bound manner. It is, therefore, necessary to ensure that persons recruited as teachers possess the essential aptitude and ability to meet the challenges of teaching at the school level. The National Council for Teacher Education had, therefore, directed that the essential qualifications for a person to be eligible for appointment as teacher in any of the schools referred to in clause (n) of section 2 of the RTE Act will be that he/she should pass the Teacher Eligibility Test. In the present study, an opinion of B.Ed. students from self-financed and Government colleges has been taken to see what is their view about the Teacher Eligibility Test. The study reveals that the majority of the B.Ed. students want TET be made compulsory, for this will help in controlling the quality of teachers in the schools and will ensure appointment of competent teacher.